Prevalence and determinants of child undernutrition and stunting in semiarid region of Brazil - Luciano Lima Correia; Anamaria Cavalcante e Silva; Jocileide Sales Campos; Francisca Maria de Oliveira Andrade; Márcia Maria Tavares Machado; Ana Cristina Lindsay; Álvaro Jorge Madeiro Leite; Hermano Alexandre Lima Rocha; Antonio José Ledo Alves da Cunha (Universidade de São Paulo, 2014)
OBJECTIVE : To analyze the evolution in the prevalence and determinants of malnutrition in children in the semiarid region of Brazil. METHODS : Data were collected from two cross-sectional population-based household surveys that used the same methodology. Clustering sampling was used to collect data from 8,000 families in Ceará, Northeastern Brazil, for the years 1987 and 2007. Acute undernutrition was calculated as weight/age < -2 standard deviation (SD); stunting as height/age < -2 SD; wasting as weight/height < -2 SD. Data on biological and sociodemographic determinants were analyzed using hierarchical multivariate analyses based on a theoretical model. RESULTS : A sample of 4,513 and 1,533 children under three years of age, in 1987 and 2007, respectively, were included in the analyses. The prevalence of acute malnutrition was reduced by 60.0%, from 12.6% in 1987 to 4.7% in 2007, while prevalence of stunting was reduced by 50.0%, from 27.0% in 1987 to 13.0% in 2007. Prevalence of wasting changed little in the period. In 1987, socioeconomic and biological characteristics (family income, mother's education, toilet and tap water availability, children's medical consultation and hospitalization, age, sex and birth weight) were significantly associated with undernutrition, stunting and wasting. In 2007, the determinants of malnutrition were restricted to biological characteristics (age, sex and birth weight). Only one socioeconomic characteristic, toilet availability, remained associated with stunting. CONCLUSIONS : Socioeconomic development, along with health interventions, may have contributed to improvements in children's nutritional status. Birth weight, especially extremely low weight (< 1,500 g), appears as the most important risk factor for early childhood malnutrition.